Article with pressure management and thermal insulation properties
By using multiple layers of thermal barriers in the battery module, the problems of thermal runaway and mechanical damage during charging and discharging of electric vehicle batteries are solved, efficient thermal management and pressure control are achieved, and the life of the battery module is extended.
Patent Information
- Application Number
- CN202380048090.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-19
- Filing Date
- 2023-06-20
- Publication Date
- 2025-02-07
AI Technical Summary
Electric vehicle batteries are prone to hot spots and thermal runaway events during charging and discharging, and the battery cells will undergo continuous expansion and retraction during the fast charging and discharging cycle, resulting in mechanical damage and battery module failure.
Using a multi-layer thermal barrier, including an insulating porous foam layer and a heat-resistant layer, the insulating porous foam layer is arranged alternately with the heat-resistant layer. The heat-resistant layer contains insulating particles, which can exhibit a pressure of at least 30kPa at 20% compression, and at 55% % compression exhibits a pressure of less than 2,500 kPa, while the cold plate takes more than 500 seconds to reach 150°C in the HCST test.
It achieves excellent thermal insulation characteristics, thermal runaway barrier performance, compressibility and pressure management characteristics, and can maintain stability under high temperature and high pressure conditions, extending the durability of the battery module.
Smart Images

Figure CN119403677A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates generally to the field of cushioning articles, and more particularly to the field of articles having pressure management and thermal insulation properties. The present disclosure also relates to methods of making such articles and their use in industrial applications for pressure and thermal management applications. Background Art
[0002] Currently, the electrification of vehicles is one of the biggest trends in the automotive industry. In this trend, the automotive industry focuses mainly on the propulsion of electrical energy supplied by batteries and the development of suitable electric vehicle batteries as energy storage devices. Electric vehicle batteries are used to power the propulsion systems of battery electric vehicles (BEVs) and hybrid electric vehicles (HEVs). These batteries, which are usually lithium-ion batteries, are designed to have high ampere-hour capacity. The trend in electric vehicle battery development is towards higher energy density (kWh / kg) in the battery to allow longer mileage to be covered and reduce the charging time of the battery.
[0003] Due to the high energy density of electric vehicle batteries and the high energy flow during battery charging or discharging, there is a risk of hot spots and thermal runaway events, in which the heat generated by the decomposition of a battery cell spreads very quickly to adjacent cells. This chain reaction can cause the entire electric vehicle to explode or catch fire.
[0004] Furthermore, during the normal life cycle of these energy storage devices, especially during the rapid charge and discharge cycles of electric vehicle batteries, the battery cells used in such battery modules tend to expand and contract continuously. These expansion / contraction cycles can subject the battery cells to considerable stress conditions, which in turn can lead not only to mechanical damage of the battery cells, but also to complete failure of the battery module.
[0005] In this context, the use of thermal management solutions has rapidly become a way to mitigate temperature rise in battery components. Various partial solutions are known. See, for example, US-A1-2007 / 0259258, US-A1-2019393574 and US-A1-2016 / 0308186. Summary of the invention
[0006] In a general embodiment, the present disclosure is directed to a multi-layer thermal barrier comprising:
[0007] one or more insulating porous foam layers,
[0008] one or more heat-resistant layers, the one or more heat-resistant layers being disposed on the thermally insulating porous foam layer,
[0009] Insulating porous foam layers are alternately connected with heat-resistant layers.
[0010] The heat-resistant layer contains insulating particles.
[0011] wherein the multi-layer thermal barrier exhibits a pressure of at least 30 kPa when subjected to a 20% compression,
[0012] wherein the multi-layer thermal barrier exhibits a pressure of less than 2,500 kPa when subjected to 55% compression, and
[0013] The cold plate takes more than 500 seconds to reach 150°C in the HCST test.
[0014] In certain embodiments, the weight ratio of the insulating porous foam layer to the heat resistant layer in the multi-layer thermal barrier is 20% to 75% in the multi-layer thermal barrier.
[0015] In other embodiments, the multi-layer thermal barrier does not have the following 3-layer construction:
[0016] The first heat-resistant layer,
[0017] a thermally insulating porous foam layer, the thermally insulating porous foam layer being adjacent to the first heat-resistant layer, and
[0018] A second heat-resistant layer is adjacent to the thermally insulating porous foam layer.
[0019] In other embodiments, the multi-layer thermal barrier has the following 3-layer construction:
[0020] The first heat-resistant layer,
[0021] a thermally insulating porous foam layer, the thermally insulating porous foam layer being adjacent to the first heat-resistant layer, and
[0022] A second heat-resistant layer is adjacent to the thermally insulating porous foam layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A multilayer thermal barrier (100) comprising a thermally insulating porous foam layer (101) and one or more heat resistant layers (102). Optionally, encapsulated with an organic polymer layer (106).
[0024] Figure 2 —Battery module 200 includes an assembly of battery cells 202. One or more multi-layer thermal barriers 201 formed from the exemplary materials described herein may be disposed between individual battery cells or groups of battery cells at one or more locations throughout the battery module.
[0025] Figure 3—Battery pack 300 includes a plurality of battery modules 302. A series of multi-layer thermal barriers 301 formed of exemplary materials described herein are configured to be placed between adjacent battery modules or on top of battery modules 302. Black rectangles represent placement of multi-layer thermal barriers on top of battery modules. Alternatively, multi-layer thermal barriers may be placed between one or more battery packs and a wall of a battery pack container (not shown).
[0026] Figure 4 - A manufacturing process for assembling a heat-resistant layer (102) of a multi-layer thermal barrier (100).
[0027] Figure 5 - Manufacturing process of assembling the insulating porous foam layer (101) of the multi-layer thermal barrier (100).
[0028] Figure 6 —Schematic diagram of the mechanical cycle test.
[0029] Figure 7 —Schematic diagram of compression test results of various comparative examples. See Table 5.
[0030] Figure 8 — Schematic diagram of compression test results of various working examples. See Table 5.
[0031] Fig. 9 — Schematic diagram of HCST test results of various comparative examples. See Table 5.
[0032] Fig.10 — Schematic diagram of HCST test results of various working examples. See Table 5. DETAILED DESCRIPTION
[0033] According to a first aspect, the present disclosure relates to a multi-layer thermal barrier comprising:
[0034] one or more insulating porous foam layers,
[0035] one or more heat-resistant layers, the one or more heat-resistant layers being disposed on the thermally insulating porous foam layer,
[0036] Insulating porous foam layers are alternately connected with heat-resistant layers.
[0037] The heat-resistant layer contains insulating particles.
[0038] wherein the multi-layer thermal barrier exhibits a pressure of at least 30 kPa when subjected to 20% compression, wherein the multi-layer thermal barrier exhibits a pressure of less than 2,500 kPa when subjected to 55% compression, and
[0039] The cold plate takes more than 500 seconds to reach 150°C in the HCST2 test.
[0040] In the context of the present disclosure, it has been surprisingly found that the multilayer thermal barrier as described above has excellent thermal insulation properties, excellent thermal runaway barrier performance, and excellent compressibility and pressure management properties. In some advantageous aspects, the multilayer construction as described above further exhibits excellent heat resistance and stability even at temperatures up to 600°C and for long periods of time exposed to heat.
[0041] The multilayer construction is further characterized by one or more of the following advantages: a) excellent buffering properties for individual battery cells when used in a battery assembly; b) excellent resistance to high compressive forces and high pressure conditions throughout the life of the battery assembly; c) the ability to maintain the foam structure of the polymer foam layer even under high pressure conditions; d) a simple and cost-effective manufacturing method based on the ready availability of raw materials and the minimization of manufacturing steps; e) a simple and versatile construction; f) excellent formulation flexibility for the polymer foam layer used herein; g) excellent construction and design of the spacer layer into a variety of Flexibility in form, size, and shape; h) the ability to fine-tune the compression characteristics of the multilayer construction for specific applications, operating conditions, and battery cell types; i) excellent pressure distribution for individual battery cells when used in battery assemblies; j) excellent processability and conversion characteristics; k) low thermal conductivity; l) the ability to be prepared at relatively low thicknesses; m) ready-to-use articles, particularly for thermal management applications; n) extended durability of energy storage assemblies using the buffer articles of the present disclosure; and o) the ability to adhere to a variety of substrates such as metal or polymer surfaces without the need for adhesion promoting processing steps or compositions.
[0042] These are particularly unexpected findings for a variety of reasons. First, good cushioning properties and resistance to high compressive forces and high pressure conditions are considered to be contradictory properties. In addition, it is generally not expected to obtain thermal insulation and thermal stability with compressible (soft) porous foam layers, especially foam layers with relatively low thickness, and more especially under applied compression.
[0043] In the context of the present disclosure, the inventors faced the technical challenge of designing a multi-layer thermal barrier construction having a delicate balance of excellent compressibility properties, resistance to high compressive forces, and thermal insulation properties.
[0044] Without wishing to be bound by theory, it is believed that these excellent properties and performance attributes are due in particular to Figure 1The invention relates to a combination of the following technical features highlighted in the specification: a) the use of a thermally insulating porous foam layer (101) having specific characteristics; and b) the use of one or more heat-resistant layers (102) having specific characteristics disposed on the thermally insulating porous foam layer. Optionally encapsulated by an encapsulating material (106). These layers may be arranged in other configurations, such as, for example, a porous foam layer (101) disposed on a heat-resistant layer (102). The components may further be stacked on top of each other.
[0045] Still not wishing to be bound by theory, it is believed that the one or more heat-resistant layers as described above advantageously act as a counterforce device for preventing or at least reducing unnecessary compressive forces experienced by the insulating porous foam layer not only during normal charge and discharge cycles of an electric vehicle battery, but also during more extreme conditions (such as thermal runaway events). More specifically, it is believed that the one or more heat-resistant layers as described above can maintain critical and minimum gaps between battery cells even under high pressure conditions, while still ensuring the appropriate cushioning properties necessary to allow the battery cells to expand and contract during their life cycle. This ability to maintain this set of properties is believed to directly and advantageously affect the excellent thermal insulation properties provided by the cushioning articles of the present disclosure.
[0046] The above detailed set of advantageous properties provided by the multi-layer constructions described herein is even more surprising considering that the aforementioned heat resistant layer(s) would be expected to adversely affect the foam structure of the insulating cellular foam layer, thereby compromising thermal barrier properties.
[0047] Therefore, the multilayer thermal barrier is suitable for various industrial applications, especially thermal management applications. The multilayer thermal barrier disclosed herein is particularly suitable for thermal management applications in the transportation industry (especially the automotive industry), especially as a thermal barrier, and more especially as a thermal runaway barrier. The multilayer thermal barrier as described herein is very suitable for use as a separator with thermal runaway barrier properties in a rechargeable energy storage system, especially a battery module. Also advantageously, the multilayer thermal barrier disclosed herein can be used to manufacture battery modules, especially electric vehicle battery modules and assemblies. In one beneficial aspect, the multilayer thermal barrier as described herein is suitable for manual or automatic processing and application (especially by fast robotic equipment), especially due to its excellent robustness, dimensional stability and handling characteristics. In some advantageous aspects, the multilayer thermal barrier can also meet challenging fire protection code standards due to its outstanding flame retardancy and thermal stability characteristics.
[0048] In one advantageous aspect, the multilayer thermal barriers used herein provide thermal insulation when subjected to the Hot Side / Cold Side Test (further defined in the Examples section). It takes more than 500 seconds to reach a temperature of 150° C. on the cold side.
[0049] In one advantageous aspect, the multi-layer thermal barriers used herein achieve a compression value of at least 60% when measured according to the Compression Test Method described in the Experimental Section when a compressive force of no more than 1000 kPa, no more than 900 kPa, no more than 800 kPa, no more than 700 kPa, no more than 600 kPa, no more than 500 kPa, no more than 400 kPa, no more than 300 kPa, no more than 250 kPa, no more than 200 kPa, no more than 150 kPa, no more than 100 kPa, no more than 80 kPa, no more than 60 kPa, or even no more than 50 kPa is used.
[0050] In another advantageous aspect, the multilayer thermal barriers used herein achieve a compression value of at least 20% when using a compressive force greater than 30 kPa, greater than 40 kPa, greater than 50 kPa, or even greater than 60 kPa when measured according to the Compression Test Method described in the Experimental Section.
[0051] In the context of the present disclosure, the term "adjacent" is intended to indicate two superimposed films or layers that are arranged directly adjacent to each other (i.e., adjacent to or in direct contact with each other), or that are not arranged directly adjacent to each other (i.e., when at least one additional film or layer (e.g., an adhesive layer) is arranged between the initial two superimposed films or layers). In the context of the present disclosure, the term "adjacent" is intended to indicate two superimposed films or layers that are arranged directly adjacent to each other (i.e., adjacent to or in direct contact with each other). The terms top layer and bottom layer or top film and bottom film are used herein to indicate the position of a layer or film relative to the surface of a substrate carrying such a layer or film during the formation of a polymer foam layer, respectively. The direction in which a movable substrate, layer or film moves is referred to herein as the downstream direction. The related terms upstream and downstream describe the position along the extension of the substrate.
[0052] Insulating porous foam layer
[0053] The thermally insulating porous foam layer used herein is not particularly limited, but certain thermally insulating porous foam layers may provide various advantages over certain other thermally insulating porous foam layers.
[0054] According to one advantageous aspect, the porous foam layer used in the present invention comprises a material that has a weight loss of no more than 70%, no more than 60%, no more than 50%, no more than 40%, no more than 30% or even no more than 25% after three minutes at 600°C when measured according to the Thermal Stability Test Method described in the Experimental Section.
[0055] The type of porous foam layer as described above is generally referred to as a heat-resistant material or a heat-resistant foam layer.
[0056] According to an exemplary aspect, the porous foam layer used in the multi-layer construction of the present disclosure comprises a material selected from the group consisting of an elastomeric material, a thermoplastic material, a thermoplastic elastomeric material, a thermoplastic non-elastomeric material, a thermosetting material, and any combination or mixture thereof.
[0057] In one advantageous aspect, the porous foam layer used in the present invention comprises a material selected from the group consisting of silicone elastomers, fluorosilicone rubbers, aromatic polyamides, polybenzimidazoles, polysulfides, polyimides, polysulfones, polyetherketones, fluorocarbons, polyisoprene, polybutadiene, polychloroprene, polyurethane, polyolefins (particularly polyethylene, polypropylene and ethyl vinyl acetate), polystyrene, and any combination or mixture thereof.
[0058] In a more advantageous aspect, the porous foam layer for use herein comprises a material selected from the group consisting of elastomeric materials.
[0059] In another more advantageous aspect, when measured according to the Compression Test Method described in the Experimental Section, the polymer foam layer used herein achieves a compression value of at least 60% when using a compressive force of no more than 1000 kPa, no more than 900 kPa, no more than 800 kPa, no more than 700 kPa, no more than 600 kPa, no more than 500 kPa, no more than 400 kPa, no more than 300 kPa, no more than 250 kPa, no more than 200 kPa, no more than 150 kPa, no more than 100 kPa, no more than 80 kPa, no more than 60 kPa, or even no more than 50 kPa. This type of polymer foam layer is generally referred to as a (relatively highly) compressible polymer foam layer (or soft polymer foam layer).
[0060] In another more advantageous aspect, the porous foam layer for use herein comprises a material selected from the group consisting of silicone elastomers, particularly silicone rubbers, more particularly organopolysiloxane polymers.
[0061] In one particularly advantageous aspect of the present disclosure, the porous foam layer used herein is a silicone rubber foam layer.
[0062] According to an advantageous aspect, the silicone rubber foam layer used herein can be obtained from a curable and foamable precursor of the silicone rubber foam layer, in particular an in-situ foamable precursor composition.
[0063] The precursor compositions for the silicone rubber foams herein are not particularly limited as long as they are curable and foamable. Any curable and foamable precursors of silicone rubber foams generally known in the art may be formally used in the context of the present disclosure. According to the present disclosure, those skilled in the art may easily identify curable and foamable precursors of suitable silicone rubber foams for use herein.
[0064] According to a further advantageous aspect, the precursor of the silicone rubber foam layer used herein is a two-part composition.
[0065] In a typical aspect, the two-part precursor composition of the silicone rubber foam is selected from the group consisting of an addition-curable two-part silicone composition, a condensation-curable two-part silicone composition, and any combination or mixture thereof.
[0066] In a preferred aspect, the precursor of the silicone rubber foam used herein comprises an addition-curing two-part silicone composition, particularly an addition-curing two-part organopolysiloxane composition.
[0067] One skilled in the art can readily identify suitable addition-curable two-part organopolysiloxane compositions for use herein as precursors to silicone rubber foams based on the following disclosure.
[0068] According to a particularly advantageous aspect of the present disclosure, the precursor of the silicone rubber foam used herein comprises:
[0069] a) at least one organopolysiloxane compound A;
[0070] b) at least one organohydrogenpolysiloxane compound B comprising at least two, in particular at least three, hydrogen atoms per molecule;
[0071] c) at least one hydroxyl group-containing compound C;
[0072] d) an effective amount of a curing catalyst D, in particular a platinum-based curing catalyst; and
[0073] e) Optional blowing agent.
[0074] In one exemplary aspect, at least one organopolysiloxane compound A used herein has the following formula:
[0075]
[0076] in:
[0077] R and R" are independently selected from C1 to C 30 A hydrocarbon group, and in particular, R is an alkyl group selected from the group consisting of methyl, ethyl, propyl, trifluoropropyl and phenyl, and optionally, R is a methyl group;
[0078] R' is C1 to C 20 an alkenyl group, and in particular, R′ is selected from the group consisting of vinyl, allyl, hexenyl, decenyl and tetradecenyl, and more in particular, R′ is a vinyl group;
[0079] R" is in particular an alkyl group, such as methyl, ethyl, propyl, trifluoropropyl, phenyl, and in particular R" is a methyl group; and
[0080] n is an integer having a value in the range of 5-1000, in particular 5-100.
[0081] In another exemplary aspect, the at least one hydroxyl-containing compound C used herein is selected from the group consisting of alcohols; polyols, particularly polyols having 3 to 12 carbon atoms and an average of at least two hydroxyl groups per molecule; silanols; silanol-containing organopolysiloxanes; silanol-containing silanes; water; and any combination or mixture thereof.
[0082] In yet another exemplary aspect, the at least one hydroxyl group-containing compound C used herein is selected from the group consisting of silanol-containing organopolysiloxanes.
[0083] According to an advantageous aspect of the present disclosure, the porous foam layer used herein can be obtained by a method comprising the following steps:
[0084] a) providing a substrate;
[0085] b) providing a first solid film and applying the first solid film to the substrate;
[0086] c) providing a coating tool having an upstream side and a downstream side, wherein the coating tool is offset from the substrate to form a gap perpendicular to the surface of the substrate;
[0087] d) moving the first solid film in a downstream direction relative to the coating tool;
[0088] e) providing a curable (and foamable) porous foam to the upstream side of the coating tool
[0089] precursor, thereby applying the precursor of the porous foam as a layer through the gap onto the substrate provided with the first solid film;
[0090] f) providing a second solid film and applying the second solid film (at least partially) along the upstream side of the coating tool such that the first solid film and the second solid film are applied simultaneously with the formation of (adjacent) layers of the precursor of the silicone rubber foam;
[0091] g) foaming or allowing a precursor of the cellular foam to foam;
[0092] h) curing or allowing the layer of the porous foam precursor to cure, thereby forming the porous foam layer;
[0093] i) optionally exposing the layer of porous foam precursor to a heat treatment; and
[0094] Optionally, the first solid film and / or the second solid film is removed from the porous foam layer.
[0095] Figure 5 Schematic diagram of an exemplary method for manufacturing a polymer foam layer (particularly a silicone rubber foam layer) and a coating device suitable for the manufacturing method is shown in FIG. The coating device 1 comprises a substrate 2, a coating tool 7 in the form of a coating knife, an unwinding roller 11 and a winding roller 12 for a first solid film 5, and an unwinding roller 9 and a winding roller 10 for a second solid film 6. (The substrate 2 is provided with a first solid film 5) The downstream direction 8 in which the first solid film moves relative to the coating tool 7 is indicated by an arrow with a corresponding reference numeral.
[0096] In a typical aspect of the present disclosure, a curable and foamable precursor 3 of a porous foam is provided to the upstream side of a coating tool 7, so that the precursor 3 of the porous foam is coated as a layer on the substrate 2 provided with the first solid film 5 through a gap. Figure 5 , a curable and foamable precursor 3 of a porous foam is represented as forming a so-called "rolling bead" at the upstream side of a coating tool 7. A second solid film 6 is applied (at least partially) along the upstream side of the coating tool 7, so that the first solid film 5 and the second solid film 6 are applied simultaneously with the formation of a layer of the precursor 3 of the porous foam. The layer of the precursor 3 of the porous foam is then allowed to foam and cure, thereby producing a porous foam layer 4, which is typically provided with the first solid film 5 on its bottom surface and the second solid film 6 on its top surface. Optionally, the layer of the precursor 3 of the porous foam may be exposed to a heat treatment, typically performed in an oven (not shown). In a typical aspect, the thickness of the porous foam layer 4 produced by the foaming of the layer of the precursor 3 of the porous foam is higher than the initial layer of the precursor 3 of the porous foam. After processing, the first solid film 5 and / or the second solid film 6 may be removed from the porous foam layer 4.
[0097] According to an advantageous aspect, the precursor of the cellular foam used herein is an in-situ foamable composition, which means that the foaming of the precursor occurs without the need for any additional compound, in particular an external compound.
[0098] According to another advantageous aspect, the foaming of the precursor of the cellular foam used herein is carried out using a gaseous compound, in particular hydrogen.
[0099] In a more advantageous aspect, the foaming of the precursor of the cellular foam used herein is performed by any of gas generation or gas injection.
[0100] According to a preferred aspect, the foaming of the precursor of the cellular foam used herein is carried out by gas generation, in particular in situ gas generation.
[0101] In an alternative aspect, the precursor of the cellular foam used herein further comprises an optional blowing agent.
[0102] The substrate used herein is not particularly limited. Based on the present disclosure, those skilled in the art can easily identify suitable substrates used herein.
[0103] In a typical aspect of the present disclosure, the substrate used herein is a temporary support for manufacturing purposes and from which the silicone rubber foam layer is separated and removed after foaming and curing. The substrate may optionally be provided with a surface treatment agent that is suitable for allowing the silicone rubber foam layer to be cleanly removed from the substrate (via the first solid film). Advantageously, the substrate used herein and providing the temporary support can be provided in the form of an endless belt. Alternatively, the substrate used herein can be a stationary (static) temporary support.
[0104] In a particular aspect of the present disclosure, the porous foam layer obtained after foaming and curing is separated from the substrate and can be wound up, for example, into a roll.
[0105] According to an advantageous aspect of the present disclosure, the substrate used herein comprises a material selected from the group consisting of polymers, metals, ceramics, composite materials, and any combination or mixture thereof.
[0106] The porous foam layer used in the present disclosure can be obtained by a method using a coating tool provided with an upstream side and a downstream side. The coating tool is offset from the substrate to form a gap perpendicular to the surface of the substrate.
[0107] The coating tool used herein is not particularly limited. Any coating tool commonly known in the art can be used in the context of the present disclosure. According to the present disclosure, those skilled in the art can easily identify suitable coating tools for use herein.
[0108] The coating tools that can be used for the present disclosure each have an upstream side (or surface) and a downstream side (or surface). In a typical aspect, the coating tool used in this article is also provided with a bottom portion, which faces the surface of the precursor of the receiving polymer foam of the substrate. The gap is measured as the minimum distance between the bottom portion of the coating tool and the exposed surface of the substrate. The gap can be substantially uniform in the transverse direction (i.e., in a direction perpendicular to the downstream direction), or it can be continuously or discontinuously changed in the transverse direction. The gap between the coating tool and the surface of the substrate is usually adjusted to regulate the thickness of the corresponding coating and other parameters, including, for example, the speed of the substrate in the downstream direction, the type of coating tool, the angle at which the coating tool is oriented relative to the normal of the substrate, and the type of substrate.
[0109] In a favorable aspect of the present disclosure, the gap formed by the coating tool with the substrate (coating tool gap) is in the range of 10 μm to 3000 μm, 50 μm to 2500 μm, 50 μm to 2000 μm, 50 μm to 1500 μm, 100 μm to 1500 μm, 100 μm to 1000 μm, 200 μm to 1000 μm, 200 μm to 800 μm or even 200 μm to 600 μm.
[0110] The coating tool used herein can be arranged perpendicular to the surface of the substrate, or it can be tilted so that the angle between the substrate surface and the downstream side (or surface) of the coating tool is in the range of 50° to 130° or even 80° to 100°. The coating tools that can be used in the present disclosure are generally solid and can be rigid or flexible. The coating tools used herein can take on various shapes, forms and sizes, depending on the target application and the expected properties of the silicone rubber foam layer.
[0111] In an advantageous aspect, the coating tool for this article comprises a material selected from the group consisting of polymers, metals, ceramics, composite materials, glass and any combination or mixture thereof. More advantageously, the coating tool for this article comprises a material selected from the group consisting of metals, particularly aluminum, stainless steel and any combination thereof. The flexible coating tool for this article is relatively thin generally and particularly has a thickness in the range of 0.1mm to 0.75mm in the downstream direction. The rigid coating tool for this article is generally at least 1mm or even at least 3mm thick.
[0112] According to a typical aspect of the present disclosure, the coating tool used herein is selected from the group consisting of a coating knife, a coating blade, a coating roller, a coating roller blade, and any combination thereof.
[0113] In an advantageous aspect, the coating tool used herein is selected from coating knives. It has in fact been found that using a coating tool in the form of a coating knife provides a more reproducible coating method and a better quality coating, which translates into a silicone rubber foam layer having advantageous properties.
[0114] In another advantageous aspect, the coating tool for use herein is selected from the group consisting of a coating roller and an air knife.
[0115] According to another advantageous aspect, the cross-sectional profile of the bottom portion of the coating tool (in particular the coating knife) in the longitudinal direction is designed so that the precursor layer is formed and excess precursor is removed. Typically, the cross-sectional profile of the bottom portion of the coating tool at its transversely extending edge facing the substrate is substantially planar, curved, concave or convex.
[0116] According to an advantageous aspect of the present disclosure, the porous foam layer of the present disclosure can be obtained by a method wherein the step of providing a curable (and foamable) precursor of the porous foam to the upstream side of a coating tool is performed immediately before the step of providing a second solid film and applying the second solid film along the upstream side of the coating tool, so that the first solid film and the second solid film are applied while forming (adjacent) layers of the precursor of the porous foam.
[0117] According to another advantageous aspect of the present disclosure, the steps of foaming or allowing the precursor of the porous foam to foam and curing or allowing the layer of the precursor of the porous foam to cure to form the porous foam layer are performed simultaneously.
[0118] The solid film used as the first solid film and the second solid film in this article is not particularly limited. Any solid film generally known in the art can be used formally in the context of the present disclosure. According to the present disclosure, those skilled in the art can easily identify suitable solid films for this article.
[0119] According to an advantageous aspect, the first solid film and / or the second solid film used in the present disclosure is an impermeable film, in particular an impermeable flexible film.As used herein, the term "impermeable" is intended to mean impermeability to liquids and gaseous compounds, in particular to gaseous compounds.
[0120] According to another advantageous aspect of the present disclosure, the first solid film and / or the second solid film used herein is selected from the group consisting of polymer films, metal films, composite films, and any combination thereof.
[0121] In a more advantageous aspect of the present disclosure, the first solid film and / or the second solid film used herein is selected from the group consisting of polymer films, in particular comprising a polymer material selected from the group consisting of thermoplastic polymers.
[0122] In yet another more advantageous aspect of the present disclosure, the first solid film and / or the second solid film used herein is a polymer film, wherein the polymer material is selected from the group consisting of polyester, polyether, polyolefin, polyamide, polybenzimidazole, polycarbonate, polyethersulfone, polyoxymethylene, polyetherimide, polystyrene, polyvinyl chloride, and any mixture or combination thereof.
[0123] In yet another more advantageous aspect of the present disclosure, the first solid film and / or the second solid film used herein is a polymer film comprising a polymer material selected from the group consisting of polyester, polyolefin (especially PP and PE), polyetherimide and any mixture or combination thereof.
[0124] In a particularly advantageous aspect, the first solid film and / or the second solid film used in the present disclosure is a polymer film comprising a polymer material selected from the group consisting of polyesters, in particular polyethylene terephthalate.
[0125] According to an advantageous aspect of the present disclosure, the porous foam layer of the present disclosure can be obtained by a method in which a first solid film is applied to the bottom surface of the layer of porous foam precursor and a second solid film is applied to the top (exposed) surface of the layer of porous foam precursor.
[0126] In a typical aspect of the present disclosure, the first solid film and / or the second solid film is in direct contact with an adjacent porous foam layer.
[0127] In another advantageous aspect of the present disclosure, the first major (top) surface and the second (opposite) major (bottom) surface of the porous foam layer and / or the first solid film and / or the second solid film are free of any adhesion promoting composition or treatment agent, in particular, free of primer compositions, adhesive compositions and physical surface treatment agents.
[0128] In another advantageous aspect of the present disclosure, the first major (top) surface and the second (opposite) major (bottom) surface of the porous foam layer and / or the first solid film and / or the second solid film comprise an adhesion promoting composition or treatment, particularly a primer composition, an adhesive composition and a physical surface treatment.
[0129] In yet another advantageous aspect of the present disclosure, the porous foam layer does not comprise any kind of intermediate layer between the first major (top) surface or the second (opposite) major (bottom) surface and the first solid film and / or the second solid film.
[0130] In a typical aspect of the present disclosure, the first solid film and the second solid film smoothly contact the corresponding surfaces of the silicone rubber foam layer with a close fit, thereby avoiding (or at least reducing) the inclusion of air between the solid films and the corresponding surfaces of the porous foam layer.
[0131] According to an advantageous aspect, the porous foam layer used herein comprises gas cavities, in particular hydrogen gas cavities, air gas cavities and any mixture thereof.
[0132] According to an advantageous aspect, the porous foam layer used herein comprises air cells having a rectangular shape in the direction of the layer thickness, ie in a direction perpendicular to the plane formed by the foam layer.
[0133] According to a further advantageous aspect, the air cavities which may be present in the silicone rubber foam layer have an elongated elliptical shape in the direction of the layer thickness.
[0134] Also advantageously, the air cavity used herein is not surrounded by any ceramic or polymer shell (other than the surrounding silicone polymer matrix).
[0135] In one particular aspect, the air cavities used herein have a mean average size (of their largest dimension) of no greater than 500 microns, no greater than 400 microns, no greater than 300 microns, no greater than 200 microns, no greater than 150 microns, no greater than 120 microns, no greater than 100 microns, no greater than 80 microns, no greater than 60 microns, no greater than 50 microns, no greater than 40 microns, no greater than 30 microns, or even greater than 20 microns (when calculated from SEM micrographs).
[0136] In another specific aspect, the mean average size (of the largest dimension) of the air cavities for use herein is in the range of 5 to 3000 microns, 5 to 2000 microns, 10 to 1500 microns, 20 to 1500 microns, 20 to 1000 microns, 20 to 800 microns, 20 to 600 microns, 20 to 500 microns, or even 20 to 400 microns (when calculated from SEM micrographs).
[0137] According to a typical aspect, the porous foam layer used in the present invention does not contain hollow cavities (surrounded by any ceramic or polymer shell), which hollow cavities are selected from the group consisting of hollow microspheres, glass bubbles, expandable microspheres, especially hydrocarbon-filled expandable microspheres, hollow inorganic particles, expanded inorganic particles, and any combination or mixture thereof.
[0138] According to one advantageous aspect, the porous foam layer used herein comprises a non-synthetic foam.
[0139] The porous foam layer used herein may contain additional (optional) ingredients or additives, depending on the target application.
[0140] In a specific aspect of the present disclosure, the porous foam layer used herein further comprises an additive, which additive is particularly selected from the group consisting of: flame retardants, softeners, hardeners, filler materials, tackifiers, nucleating agents, colorants, pigments, preservatives, rheology modifiers (particularly aluminum hydroxide, magnesium hydroxide, magnesium carbonate, magnesite, hydromagnesite, magnesite-hydromagnesite, hydrocarbite and calcium carbonate), UV stabilizers, thixotropic agents, surface additives, flow additives, nanoparticles, antioxidants, reinforcing agents, toughening agents, silica particles, glass or synthetic fibers, thermal insulation particles, conductive particles, electrical insulation particles, infrared sunscreen particles, and any combination or mixture thereof.
[0141] In one advantageous aspect, the porous foam layer further comprises a non-flammable (or non-burning) filler material. In a more advantageous aspect, the non-flammable filler material used herein is selected from inorganic fibers, in particular selected from the group consisting of mineral fibers, mineral wool, silicate fibers, ceramic fibers, glass fibers, carbon fibers, graphite fibers, asbestos fibers, aramid fibers, and any combination or mixture thereof.
[0142] According to a more advantageous aspect, the non-combustible filler material used herein is selected from the group consisting of mineral fibers, silicate fibers, ceramic fibers, asbestos fibers, aramid fibers, and any combination or mixture thereof.
[0143] According to a particularly beneficial aspect, the non-flammable filler material used herein is selected from the group consisting of mineral fibers. In the context of the present disclosure, it has surprisingly been found that polymer foams (particularly silicone rubber foams) also comprising mineral fibers have excellent heat resistance and thermal stability properties, as well as improved resistance to surface cracking and surface brittleness even after prolonged exposure to temperatures up to 600° C. Without wishing to be bound by theory, it is believed that these beneficial properties are due in particular to the excellent compatibility of the mineral fibers (particularly silicate fibers) with the surrounding polymer matrix (particularly silicone polymer matrix), which participates in densifying and mechanically stabilizing the resulting matrix.
[0144] In a particular aspect of this implementation, the non-combustible filler material used herein is included in the polymer foam in an amount ranging from 0.5 wt % to 40 wt %, 1 wt % to 30 wt %, 1 wt % to 20 wt %, 1 wt % to 10 wt %, 1 wt % to 8 wt %, 2 wt % to 8 wt %, 2 wt % to 6 wt %, or even 3 wt % to 6 wt %, based on the total weight of the precursor composition of the cellular foam.
[0145] In another exemplary aspect, the porous foam layer used herein is free of thermally conductive fillers.
[0146] According to an advantageous aspect of the present disclosure, the porous foam layer used herein has a relative humidity of not more than 500 kg / m 3 , not more than 450kg / m 3 , not more than 400kg / m 3 , not more than 380kg / m 3 , not more than 350kg / m 3 , not more than 320kg / m 3 , not more than 300kg / m 3 , not more than 280kg / m 3 , not more than 250kg / m 3 , not more than 220kg / m 3Or even less than 200kg / m 3 density.
[0147] According to another advantageous aspect of the present disclosure, the porous foam layer used herein has a relative humidity of 200 kg / m 3 Up to 500kg / m 3 , 200kg / m 3 Up to 450kg / m 3 , 200kg / m 3 Up to 400kg / m 3 , 200kg / m 3 Up to 380kg / m 3 , 200kg / m 3 Up to 350kg / m 3 , 200kg / m 3 Up to 320kg / m 3 , 200kg / m 3 Up to 300kg / m 3 , 200kg / m 3 Up to 280kg / m 3 Or even 200kg / m 3 Up to 250kg / m 3 density within the range of .
[0148] According to yet another advantageous aspect of the present disclosure, the porous foam layer used herein has a hardness (Shore 00) greater than 10, greater than 15, greater than 20, greater than 25, greater than 30, greater than 40, or even greater than 50.
[0149] According to yet another advantageous aspect of the present disclosure, the porous foam layer used herein has a hardness (Shore 00) ranging from 10 to 80, 10 to 70, 20 to 70, 25 to 60, 25 to 55, 30 to 55, 30 to 50, 30 to 45 or even 30 to 40.
[0150] According to another advantageous aspect of the present disclosure, the porous foam layer used herein has a heat transfer time to 150° C. of greater than 20 seconds, greater than 40 seconds, greater than 60 seconds, greater than 80 seconds, greater than 100 seconds, greater than 120 seconds, greater than 140 seconds, greater than 150 seconds, greater than 160 seconds, greater than 170 seconds or even greater than 180 seconds when measured according to Thermal Insulation Test Method 1 described in the Experimental Section.
[0151] According to another advantageous aspect of the present disclosure, the porous foam layer used herein has a heat transfer time up to 150° C. in the range of 20 seconds to 200 seconds, 40 seconds to 200 seconds, 60 seconds to 200 seconds, 100 seconds to 200 seconds, 120 seconds to 200 seconds, 140 seconds to 200 seconds, 160 seconds to 200 seconds, or even 160 seconds to 180 seconds, when measured according to Thermal Insulation Test Method 1 described in the Experimental Section.
[0152] According to yet another advantageous aspect of the present disclosure, the porous foam layer used herein has a thermal conductivity of no greater than 1 W / m / K, no greater than 0.8 W / m / K, no greater than 0.6 W / m / K, no greater than 0.5 W / m / K, no greater than 0.4 W / m / K, no greater than 0.3 W / m / K, no greater than 0.2 W / m / K, no greater than 0.1 W / m / K, no greater than 0.05 W / m / K or even no greater than 0.01 W / m / K when measured according to the test method described in the experimental section.
[0153] According to yet another advantageous aspect of the present disclosure, the porous foam layer used herein has a thermal conductivity in the range of 0.01 W / m / K to 1 W / m / K, 0.05 W / m / K to 1 W / m / K, 0.1 W / m / K to 1 W / m / K, 0.2 W / m / K to 1 W / m / K, or even 0.2 W / m / K to 0.8 W / m / K when measured according to the test method described in the experimental section.
[0154] According to yet another advantageous aspect of the present disclosure, the porous foam layer used herein undergoes a ceramizing process at a temperature of no greater than 600°C, no greater than 550°C, no greater than 500°C, no greater than 450°C, no greater than 400°C, no greater than 350°C, no greater than 300°C or even no greater than 250°C.
[0155] According to yet another advantageous aspect of the present disclosure, the porous foam layer used herein undergoes a ceramization process at a temperature in the range of 200°C to 600°C, 200°C to 550°C, 200°C to 500°C, 200°C to 450°C, 200°C to 400°C, 200°C to 350°C, 250°C to 350°C, or even 250°C to 300°C.
[0156] In the context of the present disclosure, it has in fact surprisingly been found that porous foam layers that are able to undergo a ceramization process, in particular at relatively low temperatures, have excellent heat resistance and thermal stability properties.
[0157] According to yet another advantageous aspect of the present disclosure, the porous foam layer used herein has a V-0 classification when measured according to the UL-94 standard flammability test method.
[0158] In one advantageous aspect, the porous foam layer used herein has a thickness of no greater than 10,000 microns, no greater than 8,000 microns, no greater than 6,000 microns, no greater than 5,000 microns, no greater than 4,000 microns, no greater than 3,000 microns, no greater than 2,500 microns, no greater than 2,000 microns, or even no greater than 1,500 microns.
[0159] In another advantageous aspect, the porous foam layer for use herein has a thickness in the range of 100 microns to 10000 microns, 100 microns to 8000 microns, 100 microns to 6000 microns, 200 microns to 5000 microns, 300 microns to 5000 microns, 300 microns to 4500 microns, 300 microns to 4000 microns, 500 microns to 4000 microns, 500 microns to 3000 microns, 500 microns to 2500 microns, 500 microns to 2000 microns, 500 microns to 1500 microns, 800 microns to 1500 microns, or even 1000 microns to 1500 microns.
[0160] According to a specific aspect of the present disclosure, the porous foam layer used herein may be provided with a first solid film and / or a second solid film. In an alternative implementation, the polymer foam layer may not be provided with either the first solid film and / or the second solid film.
[0161] As will be apparent to those skilled in the art, the porous foam layer used herein may take on a variety of forms, shapes and sizes, depending on the target application. Similarly, the porous foam layer used herein may be post-processed or converted as is customary in the art.
[0162] According to an exemplary aspect, the porous foam layer used herein may be in the form of a roll wound, in particular flat-wound around a core. The porous foam layer in the form of a wound roll may or may not be provided with a first solid film and / or a second solid film.
[0163] According to one exemplary aspect, the porous foam layer used herein can be cut into smaller pieces of various forms, shapes, and sizes.
[0164] Heat resistant layer
[0165] The multi-layer thermal barrier of the present disclosure further includes one or more heat resistant layers disposed on or adjacent to the insulating porous foam layer.
[0166] The one or more heat-resistant layers are dry-laid or wet-laid nonwoven fibrous thermal insulating single layers (e.g., in the form of a mat, sheet, tape, or three-dimensional thin-walled structure) that include a fibrous matrix of ceramic or other forms of non-metallic (i.e., not metal, metal alloy, or metal composite) inorganic fibers, thermally insulating ceramic or other forms of non-metallic (i.e., not metal, metal alloy, or metal composite) inorganic particles (these inorganic particles are uniformly, consistently, substantially, or otherwise distributed throughout the manufacturing process or to the extent permitted by the manufacturing process (e.g., there may be a small amount of particle settling on the bottom of the mat in both dry-laid and wet-laid processes) dispersed within the fiber matrix), and an organic or inorganic binder (e.g., an organic or inorganic adhesive binder, organic or inorganic binder fibers needled, stitched, or otherwise mechanically entangled into the fiber matrix to hold the fiber matrix together, etc.), which is uniformly, consistently, substantially, or otherwise dispersed within the fiber matrix throughout the manufacturing process or to the extent permitted by the manufacturing process to bind the inorganic filler particles and the inorganic fibers together, or otherwise hold the fiber matrix together before installation between battery cells, for a required time to at least withstand a required degree of handling (e.g., during an encapsulation process).
[0167] One or more heat-resistant layers may optionally be encapsulated by an organic (e.g., polymer, paper, etc.) encapsulation layer (e.g., one or more opposing interlayers, each of which is in the form of a film, a coating, an organic fiber nonwoven or woven fabric, etc.), which organic encapsulation layer encapsulates all, most or a portion of at least one or two main surfaces, and preferably also encapsulates all, most or a portion of the peripheral edge of the nonwoven fiber thermal insulation single layer to prevent or significantly reduce the shedding or loss of inorganic fibers or particles from the encapsulated nonwoven fiber thermal insulation single layer.
[0168] When the amount of inorganic fiber or particle loss is less than 10 wt%, 5 wt% or 1 wt% of the original fiber or particle content of the nonwoven fibrous thermal insulation layer, the reduction in inorganic fiber or particle shedding is significant. The thinner the organic encapsulation layer (i.e., the lower the organic content of the barrier), the better the hot test results / cold test results.
[0169] The multi-layer thermal barrier of the present invention may be used between battery modules or assemblies, or it may be positioned on top of or around the perimeter of a battery module. Figure 2 and Figure 3A battery module (200, 300) including battery cells (202, 302) is shown. Multilayer thermal barriers (201, 301) are shown positioned between adjacent battery cells (202, 302) and on top of the battery cells (202, 302), respectively. The multilayer thermal barriers can be (a) provided in a stack in a container (e.g., cardboard or other box), (b) continuously adhered to a major surface of a length of double-sided adhesive tape, the opposite major surface of the tape being protected by a release liner, or (c) sandwiched or otherwise arranged so as to be encapsulated in a series of spaced apart nonwoven fibrous thermal insulation between two opposing lengths of organic (e.g., polymer) encapsulating layers (e.g., in the form of two films, coatings, fibrous fabrics, etc.).
[0170] Inorganic binders, organic binders, or a combination of both for the heat resistant layer may include, for example, those disclosed in US 8,834,759. Examples of inorganic binders useful for dry-laid or wet-laid fiber processing may include silicone particles that convert to fusible silica when heated. Organic-inorganic hybrid binders are also useful, such as, for example, MQ 803TF, which is the co-hydrolysis product of tetraalkoxysilane (Q unit) and trimethylalkoxysilane (M unit). The chemical structure of MQ 803TF can be viewed as a three-dimensional network of polysilicic acid units terminated by trimethylsilyl groups. Some residual ethoxy and hydroxyl functions are present. The average molecular weight can be precisely controlled by the ratio of M units to Q units. This ratio is very important for For MQ 803TF, it is about 0.67.
[0171] Exemplary binder fibers include bicomponent core-sheath polymer fibers used in dry-laid processes. In wet-laid processes, ethylene vinyl acetate latex dispersion binders, bicomponent core-sheath polymer fibers, or a combination of the two may be used. When polymer binder fibers are used, the binder may be activated by heating and compressing the nonwoven fibrous thermal insulation material. Combinations of organic and inorganic binders may also be used.
[0172] Exemplary commercially available heat-resistant layers that can be used in the multi-layer thermal barrier assembly include Flame Barrier FRB-NT series, FRB-BK series, FRB-WT series, and FRB-NC series (all available from 3M Company), flexible or rigid mica papers or sheets such as NEMA 86P available from Asheville Mica, NewsPort News, VA, United States, or flexible mica sheets from USA Mica, Tekonsha, MI. United States.
[0173] As used herein, the term "inorganic" refers to ceramic or otherwise non-metallic (ie, not a metal, metal alloy, or metal composite) inorganic material.
[0174] "Thermal runaway" is a phenomenon when a battery cell undergoes an exothermic chain reaction, resulting in an uncontrollable temperature rise of the battery cell. The exothermic chain reaction can be caused by, for example, overheating of the battery cell, overvoltage of the battery cell, and mechanical puncture of the battery cell, among other reasons.
[0175] Thermal propagation is when a battery cell experiences thermal runaway, causing the remaining battery cells in the battery pack or system to experience thermal runaway.
[0176] A “thermal runaway event” is when one battery cell in a battery cell container overheats, causing a chain reaction of adjacent battery cells overheating and possibly exploding or catching fire until the number of overheated battery cells reaches a critical point of propagation, resulting in the destruction of all or more than half of the battery cells in a module or assembly of modules. Factors that cause battery cell overheating include: physical damage, application of overvoltage, overheating (internal short circuit in battery cell).
[0177] As the energy density of the battery cell increases, the temperature at which the battery cell begins to fail (e.g., from at least losing its efficiency or failing to ignite, burn, or explode) decreases. Similarly, as the energy density of the battery cell decreases, the temperature at which the battery cell begins to fail increases. For example, with a controlled ramp up of temperature, when the temperature reaches about 120°C to 130°C, the NMC811-type battery tends to begin to fail or even explode, while when the temperature reaches about 180°C, the NMC622-type battery begins to fail or even explode. For battery cells with lower energy density (e.g., NMC532-type battery cells and NMC433-type battery cells), the corresponding temperatures are higher. For physically larger battery cells or when the temperature rises rapidly, heat diffusion through the battery cell can cause the local temperature to take longer to reach a critical point. It is believed that this heat diffusion effect can cause the actual temperature at which the battery cell begins to fail or explode to be slightly higher. The thermal runaway barrier of the present invention may be required to prevent adjacent batteries from reaching temperatures in the range of about 130°C to about 150°C.
[0178] As used herein, "preventing" a thermal runaway event means preventing overheating of a single cell from causing overheating of cells adjacent to the single cell. When the adjacent cells do not reach temperatures above 130°C to 150°C, the barrier is considered to prevent a thermal runaway event.
[0179] As used herein, a “stop” thermal runaway event means that overheating of a single battery cell results in overheating of only adjacent battery cells (i.e., one or two battery cells on either side of the overheated battery cell), and the remaining battery cells in the battery module or assembly do not overheat.
[0180] As used herein, "mitigating" a thermal runaway event means that the thermal runaway event is mitigated for at least a sufficient time to allow personnel adjacent to a battery module or assembly (e.g., occupants of an electric vehicle passenger compartment) to escape to a safe distance away from the battery module or assembly before being harmed by the thermal runaway event. Once a battery cell fails (e.g., catches fire) and a thermal barrier is present, the time for any adjacent battery cell to propagate the failure (e.g., catches fire) is at least more than five minutes, and preferably more than ten minutes or even twenty minutes.
[0181] Inorganic particles can be solid, hollow or contain multiple voids. Such particles can include, for example, unexpanded expanded material particles, irreversibly or permanently expanded expanded materials, diatomaceous earth, inorganic aerogel materials, porous ceramic (e.g., silica) materials, irreversibly or permanently expanded perlite minerals, hollow ceramics or otherwise inorganic (e.g., glass) microspheres, etc. Such inorganic particles containing voids, such as those found in irreversibly or permanently expanded vermiculite, are particularly desirable. Irreversible or permanently expanded perlite mineral particles also contain voids, but perlite minerals are harder and less easily compressed than vermiculite minerals. Silica-based and other aerogel particles also contain voids.
[0182] As used herein, irreversibly or permanently expanded intumescent particles (e.g., vermiculite mineral and perlite mineral particles) refer to particles that have been heated to a temperature and time that causes the particles to irreversibly or permanently expand to at least 10% and at most 100% of their expandability, or to be pre-expanded prior to use in forming a thermal runaway barrier, or to be post-expanded after being incorporated into a nonwoven fibrous thermal insulation monolayer.
[0183] Expanded particles (e.g., vermiculite particles) can be permanently expanded by superheating the particles beyond a reversible point (e.g., in the range of about 350°C to about 1000°C for vermiculite). Such permanently expanded expanded particles (e.g., vermiculite particles) can have an expanded accordion or worm-like structure that is more easily broken into smaller particles than the same particles in their unexpanded state due to their elongated geometry, lower density, and lower mechanical stability. As the heating temperature increases, the degree of permanent expansion of the particles increases (i.e., the particles can become larger and / or longer). It may also be desirable to use vermiculite that has been permanently expanded by chemical treatment methods.
[0184] Because they are more likely to break apart in their expanded state, it may be desirable to post-expand the intumescent particles after the unexpanded intumescent particles have been incorporated into the nonwoven fibrous thermal insulation. Even with gentle processing to substantially prevent them from breaking apart, it is believed that incorporating pre-expanded intumescent particles into the nonwoven fibrous thermal insulation may still result in the intumescent particles becoming oriented into the plane of the insulation (i.e., the x-axis, the y-axis, and / or therebetween). For example, with pre-expanded vermiculite particles, the elongated particles may become generally aligned with the fibers in the longitudinal or downstream direction (i.e., the y-axis) of the nonwoven fibrous thermal insulation, rather than in the thickness direction (i.e., the z-axis).
[0185] In contrast, when expanded thereafter (i.e., after the nonwoven fiber thermal insulation is prepared with the unexpanded expanded particles), the expanded expanded particles are not primarily oriented in the plane of the insulation. Unexpanded expanded particles generally have a more uniform structural geometry (i.e., have an aspect ratio closer to 1) than the same particles in their expanded state. It is believed that this more uniform structural geometry is less likely to be affected by fiber alignment during the formation of the nonwoven fiber thermal insulation. As a result, the expanded expanded particles after expansion are more likely to be oriented isotropically within the nonwoven fiber thermal insulation. For example, with respect to the post-expanded vermiculite particles, the elongated particles may become aligned in the thickness direction (i.e., the z-axis), in the plane (i.e., the x-axis, the y-axis, and / or therebetween), or in its off-axis direction. It is believed that this difference between the orientation of the pre-expanded particles and the post-expanded particles is caused by the unexpanded particles having a more uniform structural geometry than when they are in their expanded state.
[0186] The heat resistant layer comprises inorganic fibers in an amount ranging from as low as about 15 to 19 wt % to as high as about 70, 75, 80, 85 or 90 wt % of the nonwoven fibrous thermal insulation layer.
[0187] The heat-resistant layer may contain bulk fiber particles in an amount ranging from about 3 wt % to about 60 wt % of the amount of inorganic fibers in the nonwoven fibrous thermal insulation layer.
[0188] If no insulating particles are added, the inorganic fiber content of the dry-laid web is 95.2%, and the inorganic fiber content of the wet-laid web is 95.5%. Under the lowest level of aerogel filler loading, the inorganic fiber content is 72% for dry-laid and wet-laid webs. For dry-laid nonwoven fiber thermal insulation, the fibers are opened (i.e., large pieces of fiber are separated and become less dense), which can remove some loose particles. For wet-laid nonwoven fiber thermal insulation, the fibers are wet-cleaned, which removes more loose particles than the dry-laid opening process. There are about 40% loose particles in the uncleaned SuperWool Plus from Morgan, and the actual fiber material content in the nonwoven fiber thermal insulation is 19%-43%. For nonwoven fiber thermal insulation, it may be necessary to have a fiber content in the range of about 10% to about 80%. A lower amount of fiber will require a higher amount of organic binder. Other additives (e.g., flame retardant materials, heat absorbing materials, infrared reflective materials, etc.) may be included.
[0189] The heat-resistant layer may contain inorganic thermally insulating particles in an amount ranging from as low as about 10% to as high as about 40%, 45%, 50%, 55%, or 60% by weight of the nonwoven fibrous thermally insulating layer. For example, a particle content of up to 60% may be obtained using a dry-laid process, and a particle content of up to 50% may be obtained using a wet-laid process.
[0190] The heat resistant layer may include an amount of organic binder ranging from as low as about 2.5, 3.0 or 3.5 wt % to as high as about 7.5, 8.0, 8.5, 9.0, 9.5 or 10.0 wt % of the nonwoven fibrous thermal insulation layer.
[0191] The heat-resistant layer according to any embodiment may have an installed (i.e., compressed, for example, between 2 battery cells) thickness in the range of about 0.5 mm to about 10 mm, wherein the lower limit may be about 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, and the upper limit may be about 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm or 2.5 mm. In some applications, the installed thickness may even be up to about 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm, 3.0 mm, 3.1 mm, 3.2 mm, 3.3 mm, 3.4 mm, 3.5 mm, 3.6 mm, 3.7 mm, 3.8 mm, 3.9 mm, 4.0 mm, 4.1 mm, 4.2 mm, 4.3 mm, 4.4 mm, 4.5 mm, 4.6 mm, 4.7 mm, 4.8 mm, 4.9 mm, 5.0 mm, 6 mm, 7 mm, 8 mm, 9 mm or even 10 mm. The installed thickness of the nonwoven fiber thermal insulation layer is always less than its uninstalled (i.e., uncompressed) thickness. The performance of the heat-resistant layer is measured when it is in its installed (i.e., compressed) state.
[0192] The heat-resistant layer according to any embodiment may have an uninstalled (i.e., uncompressed) thickness in the range of about 1 mm to less than 20 mm, wherein the lower limit may be about 1 mm, 1.5 mm, 2 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm, 3.0 mm, 3.1 mm, 3.2 mm, 3.3 mm, 3.4 mm, 3.5 mm, and the upper limit may be about 4.0 mm, 4.1 mm, 4.2 mm, 4.3 mm, 4.4 mm, 4.5 mm, 4.6 mm, 4.7 mm, 4.8 mm, 4.9 mm, 5.0 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, or 20 mm. The uncompressed thickness of the nonwoven fiber thermal insulation layer is always greater than its installed thickness.
[0193] The heat-resistant layer according to any embodiment may have a basis weight in the range of about 250 g / m2, 300 g / m2, 350 g / m2 or 400 g / m2 for about 1 mm gap to about 800 g / m2, 850 g / m2, 900 g / m2, 950 g / m2 or 1000 g / m2 for about 2 mm, 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm or less than 5.0 mm gap. In one embodiment, the inorganic thermal insulation particles are vermiculite, and the non-woven fiber thermal insulation layer has a basis weight of 300 g / m2 and is installed with a gap of about 1 mm. In another embodiment, the inorganic thermal insulation particles are silica aerogel, and the non-woven fiber thermal insulation layer has a basis weight of 250 g / m2 and is installed with a gap of about 1 mm.
[0194] The heat-resistant layer according to any embodiment may have a basis weight in the range of about 250 g / m2 to about 400 g / m2. Specifically, for example, when the inorganic thermal insulation particles are vermiculite and the gap is about 1 mm, a basis weight in the range of about 300 g / m2 to 400 g / m2 may be required. When aerogel particles are used and the gap is about 1 mm, a basis weight of about 250 g / m2 may also be required. When the gap is about 2.0 mm, a basis weight in the range of about 800 g / m2 to about 1000 g / m2 may be required.
[0195] The heat-resistant layer according to any embodiment is prepared from or at least includes particles of one or any combination of materials selected from the group consisting of: inorganic (e.g., titanium dioxide, zirconium oxide and / or silicon dioxide) aerogels, xerogels, hollow or porous ceramic (e.g., glass, alumina, etc.) microspheres (e.g., bubbles, foam spheres, beads, etc.), unexpanded vermiculite, irreversibly or permanently expanded vermiculite (i.e., vermiculite that has been heated to a certain temperature and for a period of time such that the vermiculite particles are irreversibly or permanently expanded to at least 10% and at most 100% of their expandability, or by forming a screen with a plurality of particles thereof. The invention also includes but is not limited to pre-expanded prior to use in forming a barrier, or post-expanded after it is in the nonwoven fibrous thermal insulating monolayer), fumed silica and other forms of porous silica, irreversibly or permanently expanded perlite (i.e., perlite that has been heated to a temperature and for a period of time such that the perlite particles irreversibly or permanently expand to at least 10% and up to 100% of its expandability, or by being pre-expanded prior to use in forming a barrier, or post-expanded after it is in the nonwoven fibrous thermal insulating monolayer), unexpanded perlite, pumice, expanded clay, diatomaceous earth, titanium dioxide, and zirconium oxide.
[0196] The heat-resistant layer according to any embodiment may comprise inorganic fibers of a fiber matrix selected from the group of fibers consisting of: alkaline earth silicate fibers, refractory ceramic fibers (RCF), polycrystalline wool (PCW) fibers, basalt fibers, glass fibers, and silicate fibers. Glass fibers and silica fibers generally do not contain any or only nominal bulk particles. PCW generally contains up to 5% bulk particles, while alkaline earth silicate (AES) fibers contain up to 60% particles when not cleaned and contain as little as about 10%-30% of minimum bulk particles when cleaned.
[0197] The heat-resistant layer according to any embodiment may include an organic binder in the form of polymer fibers (e.g., PE / PET, PET, FRPET), dry polymer powders (e.g., LDPE, polyamide, epoxy resin powders (3M SCOTCHCAST 265, 3MSCOTCHKOTE 6258)), or liquid binders (e.g., acrylic latex, ethylene vinyl acetate (EAF68) latex, silicone, polyurethane, etc.).
[0198] The heat-resistant layer according to any embodiment may be encapsulated by an organic encapsulating layer. The organic encapsulating layer is in the form of a continuous layer, a discontinuous layer (e.g., having perforations, through holes or pores that allow gas to penetrate the organic layer), or a combination of the two. In addition, the organic layer may be in the form of a film, a scrim, a woven or non-woven fabric, an adhesive (e.g., a thermoplastic or hot melt adhesive) layer, or a combination thereof. An example of an organic layer is a copolyester polymer film.
[0199] The organic encapsulant layer may be a calendared layer, a hot melt coating, a spray coating, a dip coating, or a laminated layer (eg, by using a pressure sensitive adhesive or other adhesive), and may be sealed around the peripheral edge.
[0200] The heat-resistant layer according to any embodiment passes the UL94 V0 test.
[0201] The heat-resistant layer according to any embodiment comprises inorganic thermal insulation particles made of or at least comprising particles of an irreversibly or permanently expanded intumescent material. The expanded intumescent material may expand irreversibly or permanently to a range of at least about 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90% to 100% of its expandability.
[0202] The inorganic thermal insulation particles in the heat-resistant layer may include fumed silica particles having a surface area in a range of about 100 m2 / g to about 400 m2 / g.
[0203] The heat-resistant layer according to any embodiment can be assembled by forming a nonwoven fiber thermal insulation layer using a wet-laid process or a dry-laid process. Figure 4The inorganic thermally insulating particles are arranged to be evenly or uniformly distributed throughout or within the nonwoven fibrous thermally insulating layer. The layer may be exposed to heat for a period of time to cause the unexpanded particles to expand irreversibly. Heating may occur before or after the inorganic thermally insulating particles are arranged within the nonwoven fibrous thermally insulating layer. Heating may also occur before or after the inorganic thermally insulating particles are arranged within the nonwoven fibrous thermally insulating layer.
[0204] In one particular aspect of the present disclosure, at least one expansion and / or contraction surface expands (and / or contracts) when exposed to thermal energy (heat).
[0205] According to one advantageous aspect, the cushioning articles of the present disclosure have a heat transfer time to 150° C. of greater than 20 seconds, greater than 60 seconds, greater than 100 seconds, greater than 150 seconds, greater than 180 seconds, greater than 200 seconds, greater than 240 seconds, greater than 280 seconds, greater than 300 seconds, greater than 320 seconds, greater than 340 seconds, greater than 350 seconds, or even greater than 360 seconds when measured at 0.1 MPa according to Thermal Insulation Test Method 2 described in the Experimental Section.
[0206] According to another advantageous aspect of the present disclosure, the multilayer thermal barrier has a heat transfer time to 150° C. in a range of 20 to 380 seconds, 40 to 380 seconds, 60 to 380 seconds, 100 to 380 seconds, 150 to 380 seconds, 180 to 380 seconds, 200 to 380 seconds, 250 to 380 seconds, or even 300 to 380 seconds, when measured at 0.1 MPa according to Test Method 2 described in the Experimental Section.
[0207] According to yet another advantageous aspect of the present disclosure, the multi-layer thermal barrier has a heat transfer time to 150° C. of greater than 20 seconds, greater than 40 seconds, greater than 60 seconds, greater than 80 seconds, greater than 100 seconds, greater than 120 seconds, greater than 140 seconds, or even greater than 150 seconds when measured at 1 MPa according to Thermal Insulation Test Method 2 described in the Experimental Section.
[0208] According to yet another advantageous aspect, the multi-layer thermal barrier of the present disclosure has a heat transfer time to 150° C. in a range of 20 to 180 seconds, 40 to 180 seconds, 60 to 180 seconds, 100 to 180 seconds, 120 to 180 seconds, 140 to 180 seconds, or even 140 to 160 seconds when measured at 1 MPa according to Thermal Insulation Test Method 2 described in the Experimental Section.
[0209] According to yet another advantageous aspect, the multi-layer thermal barrier of the present disclosure has a thermal conductivity of no greater than 1 W / m / K, no greater than 0.8 W / m / K, no greater than 0.6 W / m / K, no greater than 0.5 W / m / K, no greater than 0.4 W / m / K, no greater than 0.3 W / m / K, no greater than 0.2 W / m / K, no greater than 0.1 W / m / K, no greater than 0.05 W / m / K, or even no greater than 0.01 W / m / K, when measured according to the test method described in the experimental section.
[0210] In yet another advantageous aspect, the multi-layer thermal barrier of the present disclosure has a thermal conductivity in the range of 0.01 W / m / K to 1 W / m / K, 0.05 W / m / K to 1 W / m / K, 0.1 W / m / K to 1 W / m / K, 0.2 W / m / K to 1 W / m / K, or even 0.2 W / m / K to 0.8 W / m / K when measured according to the test method described in the experimental section.
[0211] In yet another advantageous aspect, the multi-layer thermal barrier of the present disclosure has a V-0 classification when measured according to the UL-94 standard flammability test method.
[0212] According to exemplary aspects of the present disclosure, the multi-layer thermal barrier has a thickness in the range of 100 microns to 20,000 microns, 100 microns to 15,000 microns, 100 microns to 10,000 microns, 100 microns to 8,000 microns, 100 microns to 6,000 microns, 200 microns to 5,000 microns, 300 microns to 5,000 microns, 300 microns to 4,500 microns, 300 microns to 4,000 microns, 500 microns to 4,000 microns, 1,000 microns to 3,000 microns, 1,000 microns to 2,500 microns, 1,500 microns to 2,500 microns, or even 2,000 microns to 2,500 microns.
[0213] According to another aspect, the present disclosure relates to a method for manufacturing a multilayer thermal barrier as described above, wherein the method comprises the following steps:
[0214] a) providing a porous foam layer as described above;
[0215] b) providing one or more heat resistant layers as described above; and
[0216] c) laminating a heat-resistant layer on one or more of the surfaces of the porous foam layer, or laminating a porous foam layer on one or more of the surfaces of the heat-resistant layer.
[0217] According to yet another aspect, the present disclosure relates to a rechargeable electrical energy storage system, in particular a battery module, comprising the multilayer thermal barrier article as described above.
[0218] In yet another aspect, the present disclosure is directed to a battery module including a plurality of battery cells separated from each other by gaps and the multi-layer thermal barrier as described above positioned in the gaps between the battery cells.
[0219] Suitable battery modules, battery subunits and methods for their manufacture for use herein are described, for example, in EP-A1-3352290 (Goeb et al.), in particular Figures 1 to 3 and paragraphs
[0016] to
[0035] , the contents of which are hereby incorporated by reference in their entirety.
[0220] According to an advantageous aspect of the battery module according to the present disclosure, the battery cells used therein are selected from the group consisting of pouch-shaped energy storage battery cells and prismatic energy storage battery cells, in particular from the group of pouch-shaped energy storage battery cells.
[0221] According to another aspect, the present disclosure relates to a method of manufacturing a battery module, the method comprising the steps of:
[0222] a) providing a plurality of battery cells separated from each other by gaps; and
[0223] b) Positioning a multi-layer thermal barrier as described above in the gaps between battery cells.
[0224] According to yet another aspect, the present disclosure relates to a method of cushioning at least one expansion (and / or contraction) surface, the method comprising the step of applying a cushioning article as described above to at least a portion of the at least one expansion (and / or contraction) surface. In a specific aspect, the at least one expansion (and / or contraction) surface expands (and / or contracts) when exposed to thermal energy (heat).
[0225] According to yet another aspect, the present disclosure relates to the use of a cushioning article as described above for industrial applications, particularly for thermal management applications, more particularly in the transportation industry, and even more particularly in the automotive, aviation and aerospace industries.
[0226] According to yet another aspect, the present disclosure relates to the use of a cushioning article as described above as a thermal barrier, in particular a thermal runaway barrier.
[0227] In yet another aspect, the present disclosure relates to the use of a buffer article as described above as a thermal barrier spacer, in particular a thermal runaway barrier spacer, in a rechargeable electrical energy storage system, in particular a battery module.
[0228] In yet another aspect, the present disclosure relates to the use of a buffer article as described above as a thermal barrier spacer, in particular a thermal runaway barrier spacer, between a plurality of battery cells present in a rechargeable electrical energy storage system, in particular a battery module.
[0229] In yet another aspect, the present disclosure relates to the use of the buffer article as described above as a buffer spacer present in a rechargeable electrical energy storage system, in particular a battery module, in particular between a plurality of battery cells.
[0230] In yet another aspect, the present disclosure relates to the use of a cushioning article as described above as a cushioning spacer for cushioning at least one expanding (and / or contracting) surface, wherein the at least one expanding surface expands (and / or contracts) particularly when exposed to thermal energy (heat).
[0231] Exemplary embodiments
[0232] 1. A multi-layer thermal barrier, comprising
[0233] one or more insulating porous foam layers,
[0234] one or more heat-resistant layers, the one or more heat-resistant layers being disposed on the thermally insulating porous foam layer,
[0235] Insulating porous foam layers are alternately connected with heat-resistant layers.
[0236] wherein the heat-resistant layer comprises insulating particles,
[0237] wherein the multilayer thermal barrier exhibits a pressure of at least 30 kPa when subjected to a 20% compression,
[0238] wherein the multi-layer thermal barrier exhibits a pressure of less than 2,500 kPa when subjected to 55% compression, and
[0239] The cold plate takes more than 500 seconds to reach 150°C in the HCST test.
[0240] 2. A multi-layer thermal barrier, comprising
[0241] one or more insulating porous foam layers,
[0242] one or more heat-resistant layers, the one or more heat-resistant layers being disposed on the thermally insulating porous foam layer,
[0243] Insulating porous foam layers are alternately connected with heat-resistant layers.
[0244] wherein the heat-resistant layer comprises insulating particles,
[0245] wherein the multilayer thermal barrier exhibits a pressure of at least 30 kPa when subjected to a 20% compression,
[0246] wherein the multi-layer thermal barrier exhibits a pressure of less than 2,500 kPa when subjected to 55% compression,
[0247] The cold plate needs at least 500 seconds to reach 150°C in the HCST test, and
[0248] The weight ratio of the thermal insulation porous foam layer to the heat-resistant layer in the multi-layer thermal barrier is 20%-75%.
[0249] 3. A multi-layer thermal barrier, comprising
[0250] one or more insulating porous foam layers,
[0251] one or more heat-resistant layers, the one or more heat-resistant layers being disposed on the thermally insulating porous foam layer,
[0252] Insulating porous foam layers are alternately connected with heat-resistant layers.
[0253] wherein the heat-resistant layer comprises insulating particles,
[0254] The cold plate needs at least 500 seconds to reach 150°C in the HCST test, and
[0255] The weight ratio of the thermal insulation porous foam layer to the heat-resistant layer in the multi-layer thermal barrier is 20%-75%.
[0256] 4. A multi-layer thermal barrier, comprising
[0257] one or more insulating porous foam layers,
[0258] one or more heat-resistant layers, the one or more heat-resistant layers being disposed on the thermally insulating porous foam layer,
[0259] Insulating porous foam layers are alternately connected with heat-resistant layers.
[0260] wherein the heat-resistant layer comprises insulating particles,
[0261] wherein the multilayer thermal barrier exhibits a pressure of at least 30 kPa when subjected to a 20% compression,
[0262] wherein the multi-layer thermal barrier exhibits a pressure of less than 2,500 kPa when subjected to 55% compression, and
[0263] The cold plate needs at least 500 seconds to reach 150°C in the HCST test.
[0264] Wherein the multi-layer thermal barrier does not have the following 3-layer construction:
[0265] The first heat-resistant layer,
[0266] a thermally insulating porous foam layer, the thermally insulating porous foam layer being adjacent to the first heat-resistant layer, and
[0267] A second heat-resistant layer, the second heat-resistant layer is adjacent to the thermally insulating porous foam layer.
[0268] 5. A multi-layer thermal barrier, comprising
[0269] one or more insulating porous foam layers,
[0270] one or more heat-resistant layers, the one or more heat-resistant layers being disposed on the thermally insulating porous foam layer,
[0271] wherein the heat-resistant layer comprises insulating particles,
[0272] wherein the multilayer thermal barrier exhibits a pressure of at least 30 kPa when subjected to a 20% compression,
[0273] wherein the multi-layer thermal barrier exhibits a pressure of less than 2,500 kPa when subjected to 55% compression, and
[0274] The cold plate needs at least 500 seconds to reach 150°C in the HCST test.
[0275] The multi-layer thermal barrier has the following three-layer structure:
[0276] The first heat-resistant layer,
[0277] a thermally insulating porous foam layer, the thermally insulating porous foam layer being adjacent to the first heat-resistant layer, and
[0278] A second heat-resistant layer, wherein the second heat-resistant layer is adjacent to the thermally insulating porous foam layer.
[0279] 6. A multi-layer thermal barrier, comprising
[0280] one or more insulating porous foam layers,
[0281] one or more heat-resistant layers, the one or more heat-resistant layers being disposed on the thermally insulating porous foam layer,
[0282] wherein the heat-resistant layer comprises insulating particles,
[0283] wherein the multilayer thermal barrier exhibits a pressure of at least 30 kPa when subjected to a 20% compression,
[0284] wherein the multi-layer thermal barrier exhibits a pressure of less than 2,500 kPa when subjected to 55% compression, and
[0285] The cold plate needs at least 500 seconds to reach 150°C in the HCST test.
[0286] The multi-layer thermal barrier has the following three-layer structure:
[0287] The first insulating porous foam layer,
[0288] a heat-resistant layer adjacent to the first thermally insulating porous foam layer, and
[0289] A second heat-resistant layer, wherein the second heat-resistant layer is adjacent to the heat-resistant layer.
[0290] 7. The multi-layer thermal barrier according to any one of the preceding embodiments, wherein the multi-layer thermal barrier exhibits a pressure of at least 30 kPa when subjected to a mechanical cycling test of 1,000 cycles.
[0291] 8. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the multilayer thermal barrier exhibits a pressure of at least 30 kPa when subjected to 20% to 80% compression during a full load / unload cycle.
[0292] 9. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the weight ratio of the thermal insulating porous foam layer to the heat resistant layer in the multilayer thermal barrier is 20%-75%, 25%-75%, or 30%-75%, or 35%-75%, or 40%-75%, or 20%-70%, 25%-70%, or 30%-70%, or 35%-70%, or 40%-70%. %, or 20%-65%, 25%-65%, or 30%-65%, or 35%-65%, or 40%-65%, or 20%-60%, 25%-60%, or 30%-60%, or 35%-60%, or 40%-60%, or 20%-55%, 25%-55%, or 30%-55%, or 35%-55%, or 40%-55%.
[0293] 10. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the multilayer thermal barrier exhibits a pressure of at least 35 KPa, or 40 KPa, or 50 KPa when subjected to 20% compression.
[0294] 11. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the multilayer thermal barrier exhibits a pressure of less than 1,750 KPa, or 1,500 KPa, or 1,250 KPa, or 1,000 KPa, or 750 KPa when subjected to 60% compression.
[0295] 12. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the multilayer thermal barrier has the following 3-layer construction:
[0296] The first heat-resistant layer,
[0297] a thermally insulating porous foam layer, the thermally insulating porous foam layer being adjacent to the first heat-resistant layer, and
[0298] A second heat-resistant layer, the second heat-resistant layer is adjacent to the thermally insulating porous foam layer.
[0299] 13. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the cold plate requires at least 100 seconds, or 200 seconds, or 300 seconds, or 400 seconds to reach 150°C in the HCST test.
[0300] 14. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the cold plate requires at least 600 seconds, or 700 seconds, or 800 seconds, or 900 seconds, or 1000 seconds to reach 150°C in the HCST test.
[0301] 15. The multi-layer thermal barrier according to any one of the preceding embodiments, further comprising an organic encapsulating layer encapsulating the multi-layer thermal barrier.
[0302] 16. The multilayer thermal barrier according to any of the preceding embodiments, further comprising an organic encapsulation layer encapsulating the multilayer thermal barrier, and wherein the organic encapsulation layer has at least one vent formed through the organic encapsulation layer, the at least one vent being positioned and sized to allow gas contained within the multilayer thermal barrier to escape from the organic encapsulation, such that the structural integrity of the organic encapsulation layer remains intact during a thermal runaway event.
[0303] 17. The multilayer thermal barrier according to any of the preceding embodiments, wherein the insulating porous foam layer comprises a material selected from the group consisting of silicone elastomers, fluorosilicone rubbers, aromatic polyamides, polybenzimidazoles, polysulfides, polyimides, polysulfones, polyetherketones, fluorocarbons, polyisoprene, polybutadiene, polychloroprene, polyurethane, polyolefins (particularly polyethylene, polypropylene and ethyl vinyl acetate), polystyrene, and any combination or mixture thereof.
[0304] 18. The multi-layer thermal barrier according to any one of the preceding embodiments, wherein the insulating porous foam layer comprises an organopolysiloxane polymer.
[0305] 19. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the thermally insulating porous foam layer is obtainable from a curable and in-situ foamable precursor.
[0306] 20. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the thermally insulating porous foam layer is obtainable by addition curing a two-part organopolysiloxane composition.
[0307] 21. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the thermally insulating porous foam layer is obtainable from a precursor comprising
[0308] a) at least one organopolysiloxane compound A;
[0309] b) at least one organohydrogenpolysiloxane compound B comprising at least two, in particular at least three, hydrogen atoms per molecule;
[0310] c) at least one hydroxyl group-containing compound C;
[0311] d) an effective amount of a curing catalyst D, in particular a platinum-based curing catalyst; and
[0312] e) Optional blowing agent.
[0313] 22. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the thermally insulating porous foam layer is obtainable from a precursor comprising
[0314] a) at least one organopolysiloxane compound A;
[0315] b) at least one organohydrogenpolysiloxane compound B comprising at least two, in particular at least three, hydrogen atoms per molecule;
[0316] c) at least one hydroxyl group-containing compound C;
[0317] d) an effective amount of a curing catalyst D, in particular a platinum-based curing catalyst; and
[0318] e) optionally a blowing agent,
[0319] Wherein the at least one organopolysiloxane compound A has the following formula:
[0320]
[0321] in:
[0322] R and R" are independently selected from C1 to C 30 A hydrocarbon group, and in particular, R is an alkyl group selected from the group consisting of methyl, ethyl, propyl, trifluoropropyl and phenyl, and optionally, R is a methyl group;
[0323] R' is C1 to C 20 an alkenyl group, and in particular, R′ is selected from the group consisting of vinyl, allyl, hexenyl, decenyl and tetradecenyl, and more particularly, R′ is vinyl
[0324] Group;
[0325] R" is in particular an alkyl group, such as methyl, ethyl, propyl, trifluoropropyl, phenyl, and in particular R" is a methyl group; and
[0326] n is an integer having a value in the range of 5-1000, in particular 5-100.
[0327] 23. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the insulating porous foam layer is formed from a precursor that undergoes foaming by a gaseous compound.
[0328] 24. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the insulating porous foam layer has a thermal conductivity of 200 kg / m 3 Up to 500kg / m 3 density within the range of .
[0329] 25. The multi-layer thermal barrier according to any one of the preceding embodiments, wherein the insulating porous foam layer has a heat transfer time to 150°C in a HCST test of 140 seconds to 200 seconds.
[0330] 26. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the insulating porous foam layer is capable of undergoing a ceramization process at a temperature in the range of 200°C to 600°C.
[0331] 27. The multilayer thermal barrier according to any of the preceding embodiments, wherein the insulating porous foam layer comprises a non-flammable filler material, in particular selected from the group consisting of inorganic fibers, in particular selected from the group consisting of mineral fibers, mineral wool, silicate fibers, ceramic fibers, glass fibers, carbon fibers, graphite fibers, asbestos fibers, aramid fibers and any combination or mixture thereof.
[0332] 28. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the insulating porous foam layer comprises a filler material selected from the group consisting of aluminum hydroxide (ATH), magnesium hydroxide (MDH), magnesite-hydromagnesite, talc, clay, boron-based flame retardants, molybdenum compounds, tin compounds, antimony compounds, expandable graphite, gypsum, calcium carbonate, carbide fillers, metals, metal oxides, sulfates, sulfides, silicates, glasses, titanates, and any combination or mixture thereof.
[0333] 29. The multi-layer thermal barrier according to any one of the preceding embodiments, wherein the heat resistant layer consists essentially of:
[0334] A nonwoven fibrous thermally insulating single layer includes a fibrous matrix of inorganic fibers, thermally insulating inorganic particles dispersed within the fibrous matrix, and a binder dispersed within the fibrous matrix to hold the fibrous matrix together.
[0335] 30. The multi-layer thermal barrier according to any one of the preceding embodiments, wherein the heat resistant layer comprises:
[0336] A nonwoven fibrous thermal insulation layer includes a fibrous matrix of inorganic fibers, thermally insulating inorganic particles of an irreversibly expanding intumescent material dispersed within the fibrous matrix, and a binder dispersed within the fibrous matrix to hold the fibrous matrix together.
[0337] 31. The multilayer thermal barrier according to any of the preceding embodiments, wherein the heat resistant layer comprises bulk fiber in an amount ranging from about 3 wt % to about 60 wt % of the amount of inorganic fiber in the nonwoven fibrous thermal insulation layer.
[0338] 32. The multilayer thermal barrier according to any of the preceding embodiments, wherein the heat resistant layer comprises fiber bulk in an amount ranging from about 3 wt% to about 60 wt% of the amount of inorganic fibers in the nonwoven fibrous thermal insulation layer.
[0339] 33. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the heat resistant layer comprises thermally insulating inorganic particles in an amount ranging from as low as about 10% to as high as about 60% by weight of the heat resistant layer.
[0340] 34. The multi-layer thermal barrier according to any one of the preceding embodiments, wherein the heat resistant layer has an uncompressed thickness in the range of about 2 mm to 10.0 mm.
[0341] 35. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the heat resistant layer has an installed thickness in the range of about 0.5 mm to about 5 mm
[0342] 36. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the heat resistant layer comprises an amount of organic binder ranging from as low as about 2.5% to as high as about 10.0% by weight of the heat resistant layer.
[0343] 37. The multi-layer thermal barrier according to any one of the preceding embodiments, wherein the heat resistant layer has a thermal conductivity as low as about 250 g / m at about 1 mm gap. 2 Up to about 1000 g / m at about 2 mm gap 2 Basis weight within the range of.
[0344] 38. The multi-layer thermal barrier according to any one of the preceding embodiments, wherein the heat resistant layer has a thermal conductivity of about 250 g / m 2 To about 400g / m 2 The uncompressed basis weight is within the range of .
[0345] 39. The multilayer thermal barrier according to any of the preceding embodiments, wherein the heat resistant layer comprises particles of one or any combination of materials selected from the group consisting of inorganic aerogels, xerogels, hollow ceramic microspheres or porous ceramic microspheres, unexpanded vermiculite, irreversibly or permanently expanded vermiculite, fumed silica, other forms of porous silica, irreversibly or permanently expanded or unexpanded perlite, pumice, irreversibly or permanently expanded clay, diatomaceous earth, titanium dioxide, and zirconium oxide.
[0346] 40. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the heat resistant layer comprises inorganic fibers in the form of a fiber matrix, and the inorganic fibers are selected from the group of fibers consisting of alkaline earth silicate fibers, refractory ceramic fibers (RCF), polycrystalline wool (PCW) fibers, basalt fibers, glass fibers, and silicate fibers.
[0347] 41. The multi-layer thermal barrier according to any one of the preceding embodiments, wherein the heat resistant layer passes the UL94 V0 test.
[0348] 42. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the heat resistant layer comprises a nonwoven fibrous thermal insulation layer comprising a fibrous matrix of inorganic fibers, thermally insulating inorganic particles of irreversibly expanding intumescent material dispersed within the fibrous matrix, and a binder dispersed within the fibrous matrix to hold the fibrous matrix together,
[0349] Wherein the expanded intumescent material has been irreversibly expanded within a range of at least about 10% to 100% of its expandability.
[0350] 43. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the heat resistant layer comprises a nonwoven fibrous thermal insulation layer comprising a fibrous matrix of inorganic fibers, thermally insulating inorganic particles of irreversibly expanding intumescent material dispersed within the fibrous matrix, and a binder dispersed within the fibrous matrix to hold the fibrous matrix together,
[0351] The inorganic thermal insulation particles include irreversibly expanded vermiculite particles.
[0352] 44. The multilayer thermal barrier according to any one of the preceding embodiments, wherein the inorganic thermal insulation particles comprise fumed silica particles,
[0353] 45. A battery module comprising the multi-layer thermal barrier according to any one of the preceding embodiments.
[0354] 46. A battery module comprising the multi-layer thermal barrier according to any one of the preceding embodiments, further comprising:
[0355] a plurality of battery cells disposed in the housing; and
[0356] The battery cells are arranged in rows, wherein a multi-layer thermal barrier is provided between adjacent battery cells.
[0357] Example
[0358] The present disclosure is further illustrated by the following examples. These examples are for illustrative purposes only and are not intended to limit the scope of the appended claims. Where applicable, brand names and trade names are shown in all capital letters and / or numbers.
[0359] Test Method :
[0360] 1) Compression test
[0361] The compression test was performed in compression mode using a tensile tester from Zwick. The sample had a diameter of 50.8 mm and a thickness of >1000 microns. The test was performed at 23°C. The upper plate of the compression tester was moved at a speed of 1 mm / min until a maximum force of 2 MPa was reached. The upper plate was then moved upwards back to the starting position at the same speed of 1 mm / min for full load / unload cycles. The compression force (in kPa) required to reach various compression values was recorded.
[0362] 2) Coating weight
[0363] Weigh a 100 cm diameter sample cut from a sample layer using a circular cutter. 2 The sample is used to measure the coating weight of the polymer foam layer. The coating weight is then converted to g / m 2 .
[0364] 3) Thickness
[0365] The minimum base area is 650mm 2 The thickness of the polymer foam layer is measured by a thickness gauge. The pressure at the base of the thickness gauge is maintained at a maximum of 725Pa.
[0366] 4) Hot Side / Cold Side Test (HCST)
[0367] In a 10 kN tensile testing machine (obtained from ZWICKROELL of Ulm, Germany), the top platen was heated to 800°C and the sample was placed on a bottom platen embedded with a thermocouple set at ambient temperature. The sample was covered with a heat shield to ensure that it stayed at ambient temperature. Before the test was performed, the thickness of the sample was measured under a load of 4.9 kPa. The heat shield was then removed and the upper platen was lowered to this thickness at a closing rate of 250 mm / min. At this point, the test was started at a test time of 0 seconds. The closing rate was then reduced to 2 mm / min and the upper platen was lowered while the pressure was maintained at 1 MPa. The time for the sample to reach a temperature of 150°C (302°F) was recorded, designated as t(150°C). As will be shown in the results, for some samples tested within a specified time period (e.g., 500 seconds), the cold plate did not reach a temperature of 150°C. In those cases, the result was recorded as more than 500 seconds for the cold plate to reach 150°C, even if the cold plate did not reach 150°C within the specified time. The bottom plate was made of stainless steel with a heat capacity of 450 J / (kg*K) and a thickness of 30 mm. The upper hot plate and the bottom cold plate had the same length and width, and each weighed 1260 g.
[0368] 5)□ Mechanical cycle test
[0369] The cyclic compression test was performed in compression mode using a material tester from ZwickRoell. The specimen had a diameter of 50.8 mm and a thickness greater than 1000 microns. The test was performed at ambient temperature (i.e., approximately 23°C). The upper plate of the compression tester was moved at a speed of 25 mm / min until a force of 0.15 MPa was reached. The upper plate was then moved up and down frequently at a rate of 1 mm / min until the required number of cycles was reached. The cycle amplitude represents the expansion and contraction of the battery cell during charge and discharge (i.e., battery cell breathing). The maximum amplitude occurs when the battery is fully discharged (state of charge SOC equal to 0%) and fully charged (100% equal to SOC). See Figure 6 (BOL means Beginning of Life, and EOL means End of Life). The full amplitude height is typically 0.5 mm and depends on the actual cell chemistry. In addition, a continuous irreversible cell swelling increases incrementally with each cycle, representing an irreversible change at the Li-ion electrode. Typical irreversible swelling is about 2% to 8% of the cell thickness and cell chemistry. Therefore, the irreversible swelling is between about 0.5 mm and about 2.0 mm. The minimum and maximum pressures are recorded and reported for each cycle.
[0370] Porous foam construction
[0371] raw material:
[0372] The following raw materials are used in the examples or can be used as substitutes for or in combination with the components used in the examples:
[0373] DOWSIL 3-8209 is a two-part room temperature curable silicone rubber foam formulation commercially available under the trade name DOWSIL from The Dow Chemical Company, Midland, MI, United States.
[0374] DOWSIL 3-8235 is another two-part room temperature curable silicone rubber foam formulation commercially available under the trade name DOWSIL from The Dow Chemical Company, Midland, Michigan, USA.
[0375] BLUESIL RT foam 3242 is an open cell silicone foam commercially available under the trade name BLUESIL from Elkem Silicones, Oslo, Norway.
[0376] COATFORCE CF30 is a silicate fiber and COATFORCE CF50 is a mineral fiber, both available from Rockwool BV, The Netherlands.
[0377] MARTINAL OL-104LEO is a finely divided aluminum trihydroxide (ATH) having a d50 in the range of about 1.7 microns to about 2.1 microns, available from Martinswerk GmBH of Bergheim, Germany under the trade name MARTINAL OL-104LEO.
[0378] IMERSEAL 74S is a surface treated calcium carbonate available under the trade name IMERSEAL from Imerys S.A., Paris, France.
[0379] Porous Foam Preparation Example :
[0380] An exemplary hand-made porous foam layer was prepared according to the following procedure:
[0381] Use SPEEDMIXER to add the identified materials (see Table 1) by weight to each component A and B of silicone foam at a speed of 1500RPM and continue for 120 seconds. CF50 is mixed with OL-104LEO. The amount of the materials by weight as identified in Table 1 is added to the 200mL two-part cartridge system (200mL F System cartridge) obtained from Adchem GmbH with a volume mixing ratio of 1:1. The two-part silicone system is mixed by a static mixer (MFH 10-18T) using a 4-bar air pressure distribution gun. After 100g of mixed silicone is released into the tank, the mixture is manually homogenized for 10 seconds using a wooden spatula. The mixture is then coated between two layers of Hostaphan RN 50 / 50 solid films with a gap thickness of 600 microns (PE1 and PE2) using a knife coater. The sheet obtained begins to expand, and the reaction is completed by placing the sheet into an 80°C forced air oven for ten minutes. Thickness, coating weight, density, thermal conductivity, and compression testing were performed and these results are also included in Table 1.
[0382] Table 1: Foam composition data and test results
[0383]
[0384] Heat-resistant layer preparation example
[0385] Table 2: Materials
[0386]
[0387]
[0388] The "General Procedure for Preparing Fiber Sheets" described in U.S. Patent Application No. 2010 / 0115900 was followed, with material substitutions as shown in Table 3. Tap water (3 liters, 18°C) and 60 grams (g) of inorganic fibers were added to a GT800 Classic blender (obtained from Rotor Lips Ltd, Uetendorf, Switzerland) and washed to a bulk content of less than 50% by weight. The blender was operated at low speed for five seconds. The resulting slurry was rinsed into an RW16 mixing container equipped with a paddle mixer (obtained from IKA-Werke GmbH, Staufen, Germany) using 1 liter of tap water (18°C). The slurry was diluted with an additional liter of tap water (18°C). The diluted slurry was mixed at a medium speed to keep the solids suspended. Defoamer (available under the trade designation "FOAMASTER 111" (0.3 grams) from Henkel, Edison, NJ) and ethylene-vinyl acetate terpolymer latex (available under the trade designation "AIRFLEX 600BP" (6.0 g, 55 wt% solids) from Air Products) were added. Flocculant was added dropwise in the amounts shown in Table 3. Thermal insulation particles were then added as shown in Table 3. The mixer speed was increased and mixing continued for 1 to 5 minutes. The paddle mixer was removed and the slurry was poured into a 20 cm x 20 cm (8 inch x 8 inch) sheet former (available from Williams Apparatus Co, Watertown, NY, United States) and drained. The surface of the sheet was drained with a rolling pin roller to remove excess water. The sheet was then pressed between blotting papers at a surface pressure of 90 kPa-97 kPa (13 psi-14 psi) for five minutes. The sheet was then dried in a forced air oven at 150°C for 10 to 15 minutes and equilibrated overnight while exposed to ambient atmosphere. The thickness and basis weight of the samples were measured at a constant pressure of 4.9 kPa and recorded in Table 4.
[0389] Table 3: Composition of heat-resistant layer (weight percentage)
[0390] SW+ EAF68 FS VERM PE3 50 5 0 45 PE4 50 5 45 0
[0391] Table 4: Heat-resistant layer parameters
[0392]
[0393]
[0394] Multi-layer thermal barrier construction
[0395] Comparative Example 1
[0396] The multilayer thermal barrier article was assembled by creating a three-layer stack of PE3. The article was subjected to compression and HCST testing and the results are shown in Table 5 and Figure 7 and Fig. 9 middle.
[0397] Comparative Example 2
[0398] The multilayer thermal barrier article was assembled by creating a three-layer stack of PE1. The article was subjected to compression and HCST testing and the results are shown in Table 5 and Figure 7 and Fig. 9 middle.
[0399] Comparative Example 3
[0400] The multilayer thermal barrier article was assembled by creating a two-layer stack of PE2 and 160 micron thick KAPTON polyimide film (obtained from DuPont, Wilmington, DE, United States). PE2 was the base layer and the polyimide film was laminated to the top. The articles were subjected to compression and HCST testing and the results are shown in Table 5 and Figure 7 and Fig. 9 middle.
[0401] Comparative Example 4
[0402] The multilayer thermal barrier articles were assembled by creating a two-layer stack of PE2 and 170 g / m2 polyaramid fiber fabric (obtained from DuPont, Wilmington, Delaware, USA). PE2 was the base layer and the polyaramid fiber fabric was laminated to the top. The articles were subjected to compression and HCST testing and the results are shown in Table 5 and Figure 7 and Fig. 9 middle.
[0403] Comparative Example 5
[0404] The multilayer thermal barrier article was assembled by creating a three-layer stack of PE2 and two 160 micron thick KAPTON polyimide films (obtained from DuPont, Wilmington, Delaware, USA). PE2 was a core layer with the polyimide film laminated to the top and bottom. The article was subjected to compression and HCST testing and the results are shown in Table 5 and Figure 7 and Fig. 9 middle.
[0405] Comparative Example 6
[0406] The multilayer thermal barrier article was assembled by creating a three-layer stack of PE2 and two 170 g / m2 polyaramid fiber fabrics (obtained from DuPont, Wilmington, Delaware, USA). PE2 was a core layer of polyaramid fiber fabric laminated to the top and bottom. The article was subjected to compression and HCST testing and the results are shown in Table 5 and Figure 7 and Fig. 9 middle.
[0407] Example 1
[0408] The multilayer thermal barrier article was assembled by creating a three-layer stack of PE1 and PE3. PE1 is a core layer with PE4 layers laminated to the top and bottom. The article was subjected to compression and HCST testing and the results are shown in Table 5 and Figure 8 and Fig.10 middle.
[0409] Example 2
[0410] The multilayer thermal barrier article was assembled by creating a three-layer stack of PE1 and PE3. PE1 is a core layer with PE2 layers laminated to the top and bottom. The article was subjected to compression and HCST testing and the results are shown in Table 5 and Figure 8 and Fig.10 middle.
[0411] Example 3
[0412] The multilayer thermal barrier article was assembled by creating a three-layer stack of PE2 and PE4. PE4 is a core layer with PE2 layers laminated to the top and bottom. The article was subjected to compression and HCST testing and the results are shown in Table 5 and Figure 8 and Fig.10 middle.
[0413] Example 4
[0414] The multilayer thermal barrier article was assembled by creating a two-layer stack of PE2 and PE4. PE4 was the base layer and the PE2 layer was laminated to the top. The article was subjected to compression and HCST testing and the results are shown in Tables 5 and Figure 7-Figure 10 middle.
[0415] Table 5: Compression and hot side / cold side test results
[0416]
Claims
1. A multi-layer thermal barrier, comprising one or more insulating porous foam layers, one or more heat-resistant layers, the one or more heat-resistant layers being disposed on the thermally insulating porous foam layer, Insulating porous foam layers are alternately connected with heat-resistant layers. wherein the heat-resistant layer comprises insulating particles, wherein the multi-layer thermal barrier exhibits a pressure of at least 30 kPa when subjected to 20% compression, wherein the multi-layer thermal barrier exhibits a pressure of less than 2,500 kPa when subjected to 55% compression, and The cold plate takes more than 500 seconds to reach 150°C in the HCST test.
2. The multilayer thermal barrier of any one of the preceding claims, wherein the multilayer thermal barrier exhibits a pressure of at least 30 kPa when subjected to a mechanical cycling test of 1,000 cycles.
3. The multi-layer thermal barrier according to any one of the preceding claims, wherein the weight ratio of the thermal insulating porous foam layer to the heat-resistant layer in the multi-layer thermal barrier is 20% to 75%.
4. The multilayer thermal barrier according to any one of the preceding claims, wherein the multilayer thermal barrier has the following 3-layer construction: The first heat-resistant layer, a thermally insulating porous foam layer, the thermally insulating porous foam layer being adjacent to the first heat-resistant layer, and A second heat-resistant layer, wherein the second heat-resistant layer is adjacent to the thermally insulating porous foam layer.
5. The multi-layer thermal barrier according to any one of the preceding claims, further comprising an organic encapsulating layer encapsulating the multi-layer thermal barrier.
6. The multilayer thermal barrier according to any of the preceding claims, wherein the insulating porous foam layer comprises a material selected from the group consisting of silicone elastomers, fluorosilicone rubbers, aromatic polyamides, polybenzimidazoles, polysulfides, polyimides, polysulfones, polyetherketones, fluorocarbons, polyisoprene, polybutadiene, polychloroprene, polyurethane, polyolefins (particularly polyethylene, polypropylene and ethyl vinyl acetate), polystyrene, and any combination or mixture thereof.
7. The multilayer thermal barrier according to any one of the preceding claims, wherein the insulating porous foam layer comprises an organopolysiloxane polymer.
8. The multilayer thermal barrier according to any one of the preceding claims, wherein the insulating porous foam layer has a heat transfer time to 150°C in the HCST test of 140 seconds to 200 seconds.
9. The multilayer thermal barrier according to any one of the preceding claims, wherein the heat resistant layer comprises: A nonwoven fibrous thermal insulation layer includes a fibrous matrix of inorganic fibers, thermally insulating inorganic particles of an irreversibly expanding intumescent material dispersed within the fibrous matrix, and a binder dispersed within the fibrous matrix to hold the fibrous matrix together.
10. The multilayer thermal barrier of any one of the preceding claims, wherein the heat resistant layer comprises bulk fibers in an amount ranging from about 3 wt% to about 60 wt% of the amount of inorganic fibers in the nonwoven fibrous thermal insulation layer.
11. The multilayer thermal barrier of any one of the preceding claims, wherein the heat resistant layer comprises thermally insulating inorganic particles in an amount ranging from as low as about 10% to as high as about 60% by weight of the heat resistant layer.
12. The multilayer thermal barrier of any one of the preceding claims, wherein the heat resistant layer comprises an amount of organic binder ranging from as low as about 2.5% to as high as about 10.0% by weight of the heat resistant layer.
13. The multilayer thermal barrier of any one of the preceding claims, wherein the heat resistant layer comprises a nonwoven fibrous thermal insulation layer comprising a fibrous matrix of inorganic fibers, thermally insulating inorganic particles of irreversibly expanding intumescent material dispersed within the fibrous matrix, and a binder dispersed within the fibrous matrix to hold the fibrous matrix together, Wherein the expanded intumescent material has been irreversibly expanded within a range of at least about 10% to 100% of its expandability.
14. The multilayer thermal barrier of any one of the preceding claims, wherein the inorganic thermally insulating particles comprise fumed silica particles.
15. A battery module comprising the multi-layer thermal barrier according to any one of the preceding claims.
Citation Information
Patent Citations
Flexible fibrous material, pollution control device, and methods of making the same
US20100115900A1
Inorganic fiber webs and methods of making and using
US8834759B2